2013
DOI: 10.1002/eji.201242990
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial control of the human pDC response to extracellular bacteria

Abstract: Plasmacytoid pre-dendritic cells (pDCs) are specialized in responding to nucleic acids, and link innate with adaptive immunity. Although the response of pDCs to viruses is well established, whether pDCs can respond to extracellular bacteria remains controversial. Here, we demonstrate that extracellular bacteria such as Neisseria meningitidis, Haemophilus influenzae, and Staphylococcus aureus activate pDCs to produce IFN-α, TNF-α, IL-6, and to upregulate CD86 expression. We observed that pDCs were present withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 31 publications
0
46
2
Order By: Relevance
“…pDCs that have been developed in the presence of type I IFN resemble Peyer’s patch pDCs, produce inflammatory cytokines, stimulate Th17 cell generation and fail to secrete IFNα after TLR engagement 202 . Therefore, factors expressed at mucosal sites inhibit type I IFN secretion by pDCs, but do not block the ability of pDCs to prime naïve T cells and trigger T Reg and Th17 differentiation 203,204 .…”
Section: Gut-associated Pdcsmentioning
confidence: 99%
“…pDCs that have been developed in the presence of type I IFN resemble Peyer’s patch pDCs, produce inflammatory cytokines, stimulate Th17 cell generation and fail to secrete IFNα after TLR engagement 202 . Therefore, factors expressed at mucosal sites inhibit type I IFN secretion by pDCs, but do not block the ability of pDCs to prime naïve T cells and trigger T Reg and Th17 differentiation 203,204 .…”
Section: Gut-associated Pdcsmentioning
confidence: 99%
“…This finding confirmed earlier reports on IFN-α secretion in response to stimulation with S. aureus in a murine DC cell line (9) and initial descriptions of S. aureus -responsive IPCs (10, 11). Michea et al further demonstrated uptake of S. aureus into pDC and secretion of IFN-α, TNF, and IL-6 (6). We further detected pDC-derived IL-1β secretion and low levels of IL-10 in response to S. aureus (7).…”
Section: Recognition Of Staphylococcus Aureusmentioning
confidence: 99%
“…Most importantly, they have made us aware of the fact that there are pDC functions beyond IFN secretion. Despite their versatility only few studies described pDC activation and addressed its role in the host response to Staphylococcus aureus (6–12). Thus, their function in the daily combat with colonizing and infecting S. aureus strains remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…cDC in Mycobacterium patients is enhanced by the presence of granzyme-B producing pDC [73]. Michea et al [119] have elegantly shown that both blood and tonsillar pDC are activated by various gram positive and negative bacteria, resulting in production of IFNa and inflammatory cytokines and to priming of CD4 ? naïve T cells.…”
Section: Pdc and Immunity To Pathogensmentioning
confidence: 99%
“…Interestingly this study showed that soluble products produced by epithelial cells could greatly reduce the cytokine and IFN response of the pDC in response to bacteria, without affecting their upregulation of co-stimulation markers and their ability to prime naïve T cells. The authors suggested that epithelial cells at mucosal surfaces may restrict the pDC local inflammatory response to bacteria but support their ability to induce an adaptive immune response [119]. The ability of activated pDC to upregulate CCR6 or CCR10 and migrate to mucosal and/or skin epithelia [120] certainly gives them the tools to tackle bacterial infections and is relevant for their role in autoimmune disease.…”
Section: Pdc and Immunity To Pathogensmentioning
confidence: 99%